2019
DOI: 10.1002/dev.21887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mothers’ experience and early‐life stress on aggression and cognition in adult male mice

Abstract: Early life is an important period for brain development and behavioral programming. Both reduced maternal care and stress in early life are risk factors for various psychiatric disorders.Here, we hypothesized that females' stressful experience in their early life can lead to a disruption of mother-offspring interactions toward their own progeny. The objective of this study is to assess the effects of mothers' past stressful experience, early-life stress alone or both on behavior in adult male mice. In this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Early-life experience can shape the developing brain and encode subsequent behavior of the individuals. Our previous studies have revealed that early-life experience leads to enhanced social behavior of females with a history of brief or prolonged maternal separation [14], and these alterations may affect the next generation too: the level of social behavior was also high (at least among males), and the social coping strategy was different in the descendants that were brought up by the mothers with a history of prolonged maternal separation [15,71]. We can theorize that the upregulation of Npas4 and Nr1d1 in females with a history of early-life stress and the corresponding enhancement of social behavior may be considered an adaptation mechanism reversing the possible aberrations caused by early-life stress.…”
Section: Resultsmentioning
confidence: 99%
“…Early-life experience can shape the developing brain and encode subsequent behavior of the individuals. Our previous studies have revealed that early-life experience leads to enhanced social behavior of females with a history of brief or prolonged maternal separation [14], and these alterations may affect the next generation too: the level of social behavior was also high (at least among males), and the social coping strategy was different in the descendants that were brought up by the mothers with a history of prolonged maternal separation [15,71]. We can theorize that the upregulation of Npas4 and Nr1d1 in females with a history of early-life stress and the corresponding enhancement of social behavior may be considered an adaptation mechanism reversing the possible aberrations caused by early-life stress.…”
Section: Resultsmentioning
confidence: 99%
“…Daily postnatal handling during the first two postnatal weeks also reduced anxiety behavior in adulthood as compared with the UC (Li et al., 2018 ). In addition, differences in rearing conditions between UC and NP animals may also play a role (Reshetnikov et al., 2020 ). In preclinical studies, a second “hit” is often necessary for the long‐term effects of neonatal pain to emerge (Williams & Lascelles, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each litter consisted of 5 to 8 animals. Pups in the stress group were subjected to prolonged separation from their mothers (3 h once a day) from PND2 to PND15 as described elsewhere [1 , 2] . Briefly, each pup was placed in an individual plastic box (11 × 7 cm) filled with bedding, whereas the dam stayed in the home cage during the separation procedure.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%